5q31.3 Microdeletion syndrome: Clinical and molecular characterization of two further cases. Issue 10 (15th August 2013) - Brown, Natasha; Burgess, Trent; Forbes, Robin; McGillivray, George; Kornberg, Andrew; Mandelstam, Simone; Stark, Zornitza
ABSTRACT The 5q31.3 microdeletion syndrome has recently emerged as a distinct clinical entity, and we report two new patients with de novo deletions of this region, bringing the total to seven. Similarly to previously reported cases, the phenotype of our patients is characterized by marked hypotonia, apnea, developmental delay, and feeding difficulties. Both patients had abnormal movements which did not correlate with epileptiform activity on electroencephalogram (EEG). Developmental brain changes on neuroimaging consisted of abnormalities predominantly affecting the white matter and frontal lobes. The 5q31.3 deleted regions overlap those of previously reported cases, and allow further refinement of the shortest region of overlap to 101 kb, including only three genes. Of these, the purine‐rich element binding protein A (PURA) gene has an established role in brain development, and we propose that haploinsufficiency for this gene is primarily responsible for the neurodevelopmental features observed. © 2013 Wiley Periodicals, Inc.